IMPLEMENTASI KEBIJAKAN GERAKAN LITERASI DI SEKOLAH DASAR - Rizqiyah, Nayla; Rendiyawati, Rindi; Agustin, Serlina (Universitas Tanjungpura, 2022)
The low interest in reading students in Indonesia is a concern for the government. The Ministry of Education and Culture continues to provide innovations to increase reading interest, especially for students. In the policy of the School Literacy Movement, Elementary School is one of the main implementing parts of the implementation as a provider of facilities, guidance, and infrastructure for students. Indeed, the School Literacy Movement in Elementary Schools has three stages or processes, namely (1) habituation; (2) Development; and (3) learning. Implementation carried out at each school will certainly experience different stages and programs implemented. Factors that influence this are the readiness of the school's physical capacity, the readiness of school residents, and the readiness of other support systems (Faizah et al., 2016). This research uses a qualitative approach with a literature study method. The activity in this research process is to collect research data that has been done regarding the implementation of the School Literacy Movement in Elementary Schools. The sources used for this research are the results of the analysis of books and journals related to the title of research on the School Literacy Movement. The data analysis technique used in this research is the reduction technique.